Promoting the independent mobility of young people with SEND: The lived experience of young people with autism, ADHD, and learning disabilities. (September 2022) - O'Toole, Sarah E.; Webster, Rob; Butcher, John; Christie, Nicola
Abstract: Introduction: Young people with special educational needs and disabilities (SEND) are at heightened risk of road traffic injury and their caregivers are often concerned about independent mobility and the safety risks it poses. This qualitative research aimed to increase understanding of the facilitators and barriers to independent mobility for 7–10 and 11-13 year-olds with SEND. Method: Thirteen young people (11 male and two female, six children 7-10 years-old and seven children 11-13 years-old) diagnosed with autism, attention deficit hyperactivity disorder (ADHD), or learning disabilities video recorded three journeys they regularly undertook and then participated in a semi-structured interview with their caregiver. A thematic analysis of travel films and interview transcripts was conducted. Results: Younger children were typically not travelling independently, but both older and younger children were anxious about independent mobility. Younger and older children with SEND demonstrated unsafe behaviours in the road, had limited awareness at times of road safety, could become overwhelmed, and required longer to process information. Conclusions: The findings informed recommendations for how to effectively support the independent mobility of young people with SEND. Children are often diagnosed with multiple conditions, and it is the profile rather than the specific diagnosis that impacts their road safety. Targeting specific behaviours rather than specific disorders may therefore be a more effective approach. Road safety was a central concern for caregivers, but it was one aspect of independent mobility and a broad focus on teaching independent mobility was preferable. Support with independent mobility and road safety should be provided by a range of people who come into contact with the young person and education may need repeating at key transition points. Highlights: Independent mobility is a source of anxiety for caregivers of children with SEND. Challenges were similar for 7–10 and 11-13 year-old children with SEND. Travel training should target specific behaviours rather than specific disorders. Home-school links should be utilised to promote consistent road safety messages. Travel training is a process not an event for children with SEND.